Combinatorial identities and quantum state densities of supersymmetric sigma models on N-folds - Abdalla, MCB; Bytsenko, A. A.; Guimaraes, MEX (Springer, 2005)
There is a remarkable connection between the number of quantum states of conformal theories and the sequence of dimensions of Lie algebras. In this paper, we explore this connection by computing the asymptotic expansion of the elliptic genus and the microscopic entropy of black holes associated with (supersymmetric) sigma models. The new features of these results are the appearance of correct prefactors in the state density expansion and in the coefficient of the logarithmic correction to the entropy.